Comparative effectiveness of radical prostatectomy with adjuvant radiotherapy versus radiotherapy plus androgen deprivation therapy for men with advanced prostate cancer. Issue 20 (25th September 2018) - Jang, Thomas L.; Patel, Neal; Faiena, Izak; Radadia, Kushan D.; Moore, Dirk F.; Elsamra, Sammy E.; Singer, Eric A.; Stein, Mark N.; Eastham, James A.; Scardino, Peter T.; Lin, Yong; Kim, Isaac Y.; et al.
Abstract : Background: Men with locally advanced prostate cancer (LAPCa) or regionally advanced prostate cancer (RAPCa) are at high risk for death from their disease. Clinical guidelines support multimodal approaches, which include radical prostatectomy (RP) followed by radiotherapy (XRT) and XRT plus androgen deprivation therapy (ADT). However, there are limited data comparing these substantially different treatment approaches. Using Surveillance, Epidemiology, and End Results (SEER)–Medicare data, this study compared survival outcomes and adverse effects associated with RP plus XRT versus XRT plus ADT in these men. Methods: SEER‐Medicare data were queried for men with cT3‐T4N0M0 (LAPCa) or cT3‐T4N1M0 (RAPCa) prostate cancer. Propensity score methods were used to balance cohort characteristics between the treatment arms. Survival analyses were analyzed with the Kaplan‐Meier method and Cox proportional hazards models. Results: From 1992 to 2009, 13, 856 men (≥65 years old) were diagnosed with LAPCa or RAPCa: 6.1% received RP plus XRT, and 23.6% received XRT plus ADT. At a median follow‐up of 14.6 years, there were 2189 deaths in the cohort, of which 702 were secondary to prostate cancer. Regardless of the tumor stage or the Gleason score, the adjusted 10‐year prostate cancer–specific survival and 10‐year overall survival favored men who underwent RP plus XRT over men who underwent XRT plus ADT. However, RP plus XRT versus XRT plus ADT was associated with higher rates of erectile dysfunction (28% vs 20%; P = .0212) and urinary incontinence (49% vs 19%; P < .001). Conclusions: Men with LAPCa or RAPCa treated initially with RP plus XRT had a lower risk of prostate cancer–specific death and improved overall survival in comparison with those men treated with XRT plus ADT, but they experienced higher rates of erectile dysfunction and urinary incontinence. Abstract : Clinical practice guidelines support multimodal therapeutic approaches for men with locally advanced or regionally advanced prostate cancer. This comparative effectiveness study using population‐based data demonstrates more favorable survival outcomes in these men who received radical prostatectomy with adjuvant radiotherapy when compared to those who received radiotherapy plus androgen deprivation therapy